Influence of Temperature and Enrichment on Storage Qualities of Soy-Enriched “Lafun”, a Protein-Enriched Cassava Product - Anyaiwe, Uche Capulet; Okoronkwo, Kennedy Ahamefula; Tibi, Emmanuel Uteh (Journal of Agriculture, Food Technology and Sustainability, 2024)
The influence of enrichment and temperature on the storage qualities of soy enriched fermented mashed lafun was investigated. Samples of the protein-enriched lafun were produced from fermented cassava obtained by soaking peeled cassava chunks in water, at ambient temperature (28 – 320C) for 2 – 5days. The enriched dried milled lafun flour was packaged in the high density polythene and stored under three different temperatures of 100C, 300C, and 400C. Samples were withdrawn at four weeks interval to measure the changes in their chemical compositions during storage. The moisture increased from 6.67 to 9.21% and 4.29 to 8.00% at 100C and 300C respectively, but followed another trend on the samples stored at 400C which decreases as the temperature increases. FFA values increased at 100C 0.50%-0.90% and 300C 0.56%-1.07%. TBA increased from 0.11-0.27, 0.12-0.67 and 0.24-0.45 mda/kg for control samples at 100C, 300C and 400C respectively, while sample supplemented with soy, increased from 0.25-0.37, 0.39-0.7 and 0.24-0.94mda/kg at 100C, 300C and 400C respectively. At higher temperature of 400C, browning increased sharply after about 16 weeks of storage from about 0.02nm to 0.017nm of change in absorbance per month (dA425). Therefore, enrichment and high temperature reduces the shelf life of lafun, which could be better stored at temperature lower than 300C than at high temperature of 400C.